Analysis of Transformational Leadership and Career Development on Employee Performance Employees With Job Satisfaction as a Mediating Variable in Regional General Hospital Dr. Pirngadi - Ida Marlina; Mesra B; Elfitra Desy Surya (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of transformational leadership and career development on employee performance with job satisfaction as a mediating variable at Dr. Pirngadi Regional General Hospital (RSUD) in Medan. This study is quantitative in nature with a survey approach, using all training department employees (n = 74) as the sample. Data were collected through questionnaires and analyzed using Partial Least Squares (PLS). The results showed that transformational leadership and career development had a positive and significant effect on employee performance and job satisfaction. Job satisfaction was also found to mediate the relationship between transformational leadership and career development with employee performance. The R² value for job satisfaction was 0.491 and for employee performance was 0.635, indicating that the independent variables had a fairly strong effect on the dependent variables. This study recommends that Dr. Pirngadi Regional General Hospital improve employee understanding of work procedures, review the salary and compensation system, expand training programs, and develop the transformational leadership capacity of leaders to optimize employee performance.